Vehicle Speed Tracking Using Gps in Android Smart Phone - S.Kayathri, Mrs.; S.Girija, Mrs.; S.Meena, Ms. (International Journal of Engineering and Technology, 2018)
In the day today life, people are busy with stress work. The user can ride the bike in a very high speed without knowledge due to late wakeup in the morning and other depressions. Obviously, the high speeds of driving leads to lots of accidents. To reduce such accidents, In the android application has to plan to develop a mobile app which gives an alert to the user who is driving the bike and to send SMS to the traffic police officer and parents, when the person crosses the given input speed limit with the help of GPS, traffic police officer and parents can track the vehicle running location and time, where the vehicle violates the traffic rules. May be in future, the application will be a part of vehicle with the option enable and disable.In the recent year, tracking technique is mostly applied in android application. Smart phones are using the same global Â Â positioning system like google maps and GPS tools. This application security measure can be applied in a single finger touch. Beyond this application easily implement route tracking technique, geo fencing, vehicle locking, accident location finding can be applied in the android applications.Â
Keywords: Android; SMS; Vehicle; GPS